Pregnant adolescents in the City of Bucaramanga, Colombia. A - Ricardo Ortiz Serrano; Nathalia Isabel Anaya Ortiz; Carolina Sepúlveda Rojas; Silvia Judith Torres Tarazona; Paul Anthony Camacho López (MedUNAB, 2005)
Many social, cultural and family factors, deeply affect all pregnantadolescents. Therefore a strong support from their families, isurgently needed. Objective: To establish among pregnant adolescents,their demographic, social and family characteristics. Theseteenagers attend a primary care clinic at the City of Bucaramanga.Methods: Cross-sectional study using a self-applied questionnaire.Results: We analyze 336 pregnant adolescents, mean age 17 years(range 13 to 19). Most of them were having their first pregnancy.The mean age for their first sexual relations was at 15 years of age.65.5% of them said they had only one sexual partner. 62.2% werelife partners. 52.15% had or were attending high school. 61.6% hadsome information about pregnancy planning. 31.44 had informationfrom their school. 66.2% followed no planning at all. 59.0% washoping to get pregnant. 26.1% of them had experienced interfamilyviolence and 33.8% said they had a sister with pregnancy duringadolescence. Discussion: an important number of adolescentswant to get pregnant and establish a new home with their partners.Basically they try to get away from their violent original homes. Their partners are usually, older than the adolescent pregnant is. Most of the partners accept, worry, support and have stable relations during the girl’s pregnancy. A good and sound control for preventing teenage-pregnancy should be implemented in family programs for pregnancy planning, including prevention of sexually transmitted diseases and cervical cytology